Method to determine the weakness planes effect on the calculation of the collapse pressure of oil wells - Velilla-Uribe, Juan-David; Cáceres-Montero, Jorge-Luis; Sandoval-Merchán , Publio-Alejandro; Corzo-Rueda, Reinel; Calderón-Carrillo, Zuly-Himelda (CT&F - Ciencia, Tecnología y Futuro, 2020)
Given the complexity involved when modeling heterogeneous and anisotropic formations, this condition is usually ignored, supposing that the well is surrounded by a homogenous and isotropic medium. The main objective of this paper is to present a method that shows the error that might occur when the condition of homogeneity and isotropy is not satisfied, when determining collapse pressure in a formation containing planes of weakness. Although the literature presents some studies, there is not a clear method for determining the collapse pressure of a well that takes into account the mechanical properties of the planes of weakness contained in the formation. The proposed method is based on the Mohr Coulomb criterion for homogeneous and isotropic formations and the criterion of Jaeger and Cook (1979) for laminated anisotropic media. It constitutes a robust tool that calculates the collapse pressure in highly complex configurations, contributing thus to prevent waste of time and money by more accurately considering the actual behavior of laminated formations. The method includes: the deduction of the direction cosine equation, the proposal of an objective function, the construction of a collapse pressure profile, and the sensitivity analysis of the collapse pressure with colored rosettes. A real case was selected to implement the proposed method.